THE INFLUENCE OF SOCIAL INTERACTION ON WRITING DEVELOPMENT: THE ROLE OF COLLABORATIVE LEARNING - Nugroho Nugroho (Premise: Journal of English Education and Applied Linguistics, 2025)
This quasi-experimental study investigates how controlled peer interaction through round-robin methodology affects writing development, contrasting with conventional solitary approaches. Using a mixed-data types design, 120 intermediate-level students were divided into experimental (n=60) and control (n=60) groups. Quantitative pre- and post-tests assessed writing fluency, coherence, and complexity, while qualitative observations examined turn-taking equality, feedback quality, and nonverbal engagement. Results showed the experimental group achieved significant improvement with mean gains of 37.66 points versus 19.04 points in the control group (p<0.001). The experimental group's normalized learning gain (N-Gain) reached 77.69%, nearly double the control group's 39.36%. Qualitative findings revealed the experimental class demonstrated high turn-taking equity (63.3% balanced participation), constructive feedback (58.3% specificity), and active nonverbal engagement (66.7% eye contact, open posture), contrasting sharply with control-group dominance hierarchies (38.3% low equity) and superficial feedback (43.3% vagueness). Grounded in Vygotsky's socio-cultural theory, the study demonstrates how structured peer collaboration democratizes participation and scaffolds writing skills through critical discourse, supporting round-robin techniques as effective writing instruction that balances independence and interdependence.